MADRASA TEACHER'S SWOT IN GROWING THE SPIRIT OF LEARNING FIQH IN MILLENIAL GENERATION IN TULUNGAGUNG - Muh Khoirul Rifa’i (Al'Adalah, 2019)
In the learning process, passion and interest are one of the most important dynamic aspects. With enthusiasm and interest in students, learning results will be maximized. Thus, the teacher must know the form of enthusiasm and interest that how should be used to foster student enthusiasm for learning. Given that by providing enthusiasm and interest, students can develop activities and initiatives and can maintain perseverance in conducting learning activities and so students do not feel bored with the subject of Fiqh. These conditions will affect students' understanding of the subject of jurisprudence. If students truly understand and practice what is contained in it that is fiqh, then students will be able to carry out religious commands properly according to the commands of Allah SWT. Departing from the facts and descriptions above, the researchers are interested in studying and conducting research on "Madrasah Teacher's SWOT In Fostering the Spirit of Learning Jurisprudence in Millennial Generation in Tulungagung". In teaching and learning activities, as a teacher of Islamic education, he must be able to optimize his role when in class. One of them is as a motivator, meaning that teachers should be able to provide encouragement to students to be passionate and active in learning. In an effort to provide motivation, the teacher must be able to analyze the motives behind the students who are always lazy to learn and decline in school performance. Motivation can be effective if it is done by paying attention to students' needs. Diversification of ways of learning provides reinforcement and so on, can also provide motivation for students to be more passionate in learning. Besides, the lesson material delivered without regard to the use of the method will also make it difficult for teachers to achieve learning objectives.